A Socio-environmental Case for Skill in Outdoor Adventure. (June 2014) - Mullins, Philip M.
In response to the crisis of sustainability, this paper revisits understandings of human–environment relations established through skill-based outdoor activities that are used commonly among adventure recreation, education, and tourism. Reconsidering a predominant focus on risk and a persistent tension between technical and environmental knowledge, a case is made for skill as an important avenue for research related to participants' environmental learning and engagement. Diverse qualitative and quantitative research literature concerning outdoor education, recreation specialization, place, and skilled performance are reviewed. The author argues that developing theoretical and practical approaches to outdoor adventure education, recreation, and tourism within a sustainability paradigm will require perspectives that position humanity as belonging within environments, and that skill provides an important avenue for doing so. Ultimately, research and practice will need to account for skill development and performance as shaping—for better or worse—participants' socioecological engagement.